Mapping and tracing Grem1+ stromal cells in an ApcMin/+ mouse utilizing cryopreserved intestinal sections prepared via modified Swiss-roll technique - Youheng Jiang; Zhang Fu; Yanfang Chen; Qunlong Jin; Yanming Yang; Zerong Lin; Changxue Li; Yunfei Gao; Zepeng Dong; Yang He; Xinjun Mao; Yulong He; et al. (iScience)
Summary: Grem1+ cancer-associated fibroblasts (CAFs) are crucial in colorectal cancer (CRC) development, yet technical challenges have limited understanding of their origins, spatiotemporal distribution, and potential roles. Here, we devised a custom mold, optimizing the gut Swiss-roll technique to create a single cryopreserved slide for comprehensive staining. Our integrated approach uncovered a marked increase in Grem1+ CAFs within ApcMin/+ mouse tumors at 12 weeks, compared to normal mucosa. Subsequent lineage tracing in Grem1-CreERT2; R26-LSL-tdTomato; ApcMin/+ mice revealed that most Grem1+ CAFs infiltrating the tumor core originated from Grem1+ intestinal reticular stem cells (iRSCs). A minor subset of Grem1+ CAFs, located in the submucosa, retained characteristics of Grem1+ intestinal sub-epithelial myofibroblasts (ISEMFs). Altogether, CAFs derived from Grem1+ iRSCs may serve as a principal stromal cell type driving early-stage CRC progression, while Grem1+ ISEMFs contribute less from a more distant location. Hence, targeting Grem1+ CAFs presents an early and promising therapeutic strategy in CRC.